1987
DOI: 10.1037/0882-7974.2.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in target identification as a function of retinal location and noise level: Examination of the useful field of view.

Abstract: Foveal and peripheral target detection were compared in young adults (M age = 22 years) and older adults (M age = 66 years) who were optically corrected for the viewing distance. In a two-alternative, forced-choice task, target letters were presented at 0 degree to 10.5 degrees from fixation. Targets were presented alone, flanked on each side by one noise element (i.e., nontarget letter), or embedded in a horizontal row of 19 noise elements. An Age X Noise Level X Location interaction was obtained, wherein age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
92
1
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(108 citation statements)
references
References 16 publications
(20 reference statements)
14
92
1
1
Order By: Relevance
“…This was in contrast to the older group, who exhibited less rigorous information processing and a reliance on more general, directional-based, cues. These findings extended previous research, which has tended to focus more on age-related performance variability, such as with contrast sensitivity (Greene & Madden, 1987;Owsley, Sekuler, & Siemsen, 1983), useful field of view (Ball, Owsley, & Beard, 1990;Scialfa, Kline, & Lyman, 1987), stereopsis (Schieber, 1991), and overall attention capacity (Madden, 1986). However, in regards to 360-degree awareness, the study supported findings by Bao & Boyle (2009), who found older drivers to exhibit less usage of their review mirrors.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…This was in contrast to the older group, who exhibited less rigorous information processing and a reliance on more general, directional-based, cues. These findings extended previous research, which has tended to focus more on age-related performance variability, such as with contrast sensitivity (Greene & Madden, 1987;Owsley, Sekuler, & Siemsen, 1983), useful field of view (Ball, Owsley, & Beard, 1990;Scialfa, Kline, & Lyman, 1987), stereopsis (Schieber, 1991), and overall attention capacity (Madden, 1986). However, in regards to 360-degree awareness, the study supported findings by Bao & Boyle (2009), who found older drivers to exhibit less usage of their review mirrors.…”
Section: Introductionsupporting
confidence: 74%
“…In regards to the potential lack of awareness by the older drivers of safety-related cues, as has already been alluded to above, the literature has tended to focus on particular age-related deficits, such as useful field of view (Ball, Owsley, & Beard, 1990;Scialfa, Kline, & Lyman, 1987), and overall attention capacity (Madden, 1986). Studies have also shown, however, that older drivers make less glances towards peripheral, than their central, visual field -where they were found to hold significantly longer mean fixation durations (Maltz & Shinar, 1999).…”
Section: How Do the Findings Relate To What Has Been Found In The Litmentioning
confidence: 99%
“…Numerous studies have demonstrated that older adults have difficulty processing peripheral targets relative to young adults when the target is embedded in noise (12)(13)(14)(15)(16)(17). The findings from these studies are taken as evidence that age differences in visual search are not solely attributable to selective attention deficits.…”
Section: Introductionmentioning
confidence: 65%
“…Cole and Hughes (1984) found that the eccentricity effect was not eliminated when the size ofthe peripheral targets was increased to compensate for the decline in visual acuity and sensitivity with eccentricity. Moreover, such variables as age (Ball, Roenker, & Bruni, 1990;Madden, 1992;Scialfa, Kline, & Lyman, 1987), mental load (Egeth, 1977;Logan, 1978), and stress (Bursill, 1958) all have an impact on search performance that seems to be largely independent of their effects on such measures as acuity. These studies, like the UFOV studies, use tasks that are quite different from the standard search tasks in which an observer searches for a target item among a variable number of distractor items.…”
mentioning
confidence: 99%